KESELAMATAN KONSTRUKSI: KONSEPSI DAN REGULASI - Endroyo, Bambang (Jurnal Teknik Sipil dan Perencanaan, 2009)
Accident rate in Indonesia, specially at construction sector, was very bad. Therefore,seriuosly action for the minimization of construction accident must be done. In the year of 2009,Department of Public Work have theme: "Going to Indonesia Construction with quality byEmphasizing a Occupational Safety and Health". The expected target is the recovery ofconstruction safety in I